Application of chained functions to low-cost microwave band-pass filters using standard PCB etching techniques - Chrisostomidis,CE; Guglielmi,M; Young,PR; Lucyszyn,S (IEEE, 2007)
In this paper, the application of the chained function polynomials to the design of low-cost microwave band-pass filters is presented. The chained function concept provides a variety of transfer functions to choose from, each one having different characteristics and different implementation requirements. Thus, reduced sensitivity to manufacturing tolerances can be achieved by selecting the appropriate transfer function for a given manufacturing technology. The achieved reduction is confirmed experimentaly at millimetre-wave frequencies, using parallel-coupled line band-pass filter designs manufactured using standard PCB etching techniques.